Computer-aided design of post-tensioned, prestressed concrete flat slab and flat plate by the ACI 318-71 - Coo, Benito K. (1976)
The purpose of this thesis is to provide a computer program for the analysis and design of prestresses post-tensioned frame by ACI 318-71. The stiffnesses of columns and slabs are computed using equivalent frame method. The slope-deflection method and statics are used to derive the structure stiffness matrix equation for the frame which is specifically a traditional matrix. Fixed-end moments are computed using the column analogy method. Rotations are computed using a special simultaneous equation solver for tridiagonal systems. End moments are obtained by back substituting rotations into slope-deflection equations.
The method of analysis and design of post-tensioned members is a combination of Lin's balancing method and moment balancing. This thesis is based on the following assumptions: 1. During the prestressing operation the supports are restrained against vertical movements. 2. Frictional force is negligible, that is, the prestressing force is the same throughout the length of the structure. 3. The reduction of the cross-sectional area because of the cable ducts is negligible. 4. Reverse parabolic tension drape profiles are used. 5. The stresses throughout the slabs due to all combinations of loads are calculated on the basis of the assumption that concrete is an elastic material. These calculated stresses are to be less than or equal to the allowable stresses. 6. Design and analysis conform to the ACI 318-71. 7. The columns and slabs have infinite moment of inertia within the confines of the joints. 8. Columns should either be rectangular or circular cross-section. 9. Minimum coverage for the tendons are at midspan. 10. Adjacent spans have the same depths. 11. This program is limited to flat plate or flat slab with or without cantilevers. The structure stiffness matrix must be a tridiagonal matrix.
Appendix A-C: p. 44-174.
Photocopy.
Thesis (M.S.)--University of the Philippines, Quezon City.
Keywords: Reinforced concrete construction -- Computer programs